Capsular closure after hip arthroscopy: our experience. - Di Benedetto, Paolo; Zangari, Andrea; Giardini, Piero; Mancuso, Francesco; Castriotta, Luigi; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: In the last decade, arthroscopic treatment of hip diseases has significantly spread and evolved and currently it represents the gold standard for the treatment of femoral- acetabular impingement. In the recent years, the function of the joint capsule (and therefore the results of an arthroscopic capsulotomy) has been hugely developed, opening a heated debate. The Literature is still torn about the need for a capsular suture, but more recent studies are more oriented in its execution at the end of the surgical procedure. According to these recent studies, the joint capsule performs an essential function of primary stability, and its closure is therefore necessary to restore the native anatomy and physiology. Nevertheless, capsular management remains a controversial topic. This is a retrospective study with the aim of assessing the influence of capsular suture on the patient’s functional outcome in a cohort of patients with femoral-acetabular impingement arthroscopically treated. Hypothesis: Our hypothesis is that an adequate capsular suture positively influences the patient’s functional outcome. Methods and Results: 50 patients treated with hip arthroscopy for femoral-acetabular impingement have been retrospectively enrolled at the Orthopaedic Clinic of Academic Hospital of Udine during a period of two-years (2017-2018); collected data have been analysed and compared with a retrospective model. Patients have been divided into two equivalent groups, 25 treated with capsular suture, 25 without performing the suture. Patient’s post-operative functional outcome has been analysed using the modified Harris Hip Score (mHHS), the Non-Arthritic Hip Score (NAHS) and the Hip Outcome Score-Sport Scale (HOS-SS). The functional outcome in patients where capsular sutures were performed was better than in non-sutured patients, in all three analysed scales. Conclusions: Capsular suture with a single side-to-side stitch at the end of the procedure can positively influence the patient’s functional outcome.